(untitled) (Geography and Tourism, 2021)
Zakopane, the largest town in the Tatra County, located at the foot of the northern slope of the Tatra Mountains, i.e. the highest mountains in Poland, is characterised by the frequent occurrence of high atmospheric air pollutant concentrations, and the resulting poor aerosanitary conditions, particularly in winter months. The aim of this study is to demonstrate the relationship between the occurrence of a foehn-type wind, which is called halny in the area of the Tatra Mountains and the Podhale region, and changes in concentrations of pollutants found in the atmospheric air in Zakopane, based on the example of PM2.5 and PM10 particulate matter. The concentrations of the analysed substances in the town of Zakopane were compared on the days when foehn wind occurred on the Kasprowy Wierch peak and on the days when the foehn wind did not occur on the above-mentioned peak. The study initially showed the existence of a relationship between halny velocity on the Kasprowy Wierch peak (1987 m a.s.l) and its effects on the air quality in the town of Zakopane. Decreases in concentrations of PM2.5 and PM10 particulate matter were noted on the days when foehn wind velocity on the Kasprowy Wierch peak was equal to or exceeded 20 m·s−1.